Benefits of Using an Early Palliative Care Intervention in Pediatric Oncology. Issue 4 (August 2015) - Madden, Jennifer R.; Vaughn, Eric A. apG.; Northouse, Brent; Tong, Suhong; Dorneman, Laura A.; Foreman, Nicholas K.; Rush, Sarah Z.; Hendricks-Ferguson, Verna L.
<x xml:space="preserve">Abstract</x> Early palliative care (PC) interventions can foster effective symptom management during oncology treatments. Children with cancer are an appropriate population to receive early PC interventions to minimize suffering and foster quality of life during oncology treatments. Delivery of cisplatin along with posthydration (PH) intravenous fluids (IVFs) is an example of an early PC intervention for children diagnosed with standard risk medulloblastoma. In this study, we performed a retrospective chart review to evaluate the impact of outpatient delivery of cisplatin and PH IVF on target outcomes (renal function, ototoxicity, and health care costs) for 45 pediatric patients with standard risk medulloblastoma. Evaluation of physical outcomes revealed (a) no significant changes in serum creatinine, (b) no signs of hemorrhagic cystitis or renal insufficiency, and (c) no significant increase in signs of ototoxicity. Evaluation of health care costs revealed a reduction in the number of required hospital admissions for pediatric patients receiving outpatient cisplatin and PH IVF. In summary, PH IVF after delivery of cisplatin seems to be a potentially effective early PC intervention that may benefit the pediatric oncology patient by preserving renal function, reducing the risk of ototoxicity, and reducing health care costs because of the decreased number of hospital admissions related to outpatient delivery of cisplatin treatments.